2014
DOI: 10.1002/tox.22069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental exposure to diazepam on the reproductive behavior of fathead minnow, Pimephales promelas

Abstract: Pharmaceutical drugs are continuously discharged into the aquatic environment primarily through wastewater discharge; therefore, their possible effects on wildlife is a reason of concern. Diazepam is a widely prescribed benzodiazepine drug used to treat insomnia and anxiety disorders, and it has been found in wastewater effluents worldwide. The present study tested the effects of diazepam on fecundity and the reproductive behavior of the fathead minnow, Pimephales promelas, a fish that exhibits male parental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
(63 reference statements)
3
6
0
1
Order By: Relevance
“…Furthermore, the fecundity of R. balthica does not seem to be disturbed by oxazepam exposure. Similar observations have already been reported for fathead minnows exposed to diazepam (Lorenzi et al, 2014). However, it should be noted that hatching rates in control and the lowest concentration were significantly lower than expected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the fecundity of R. balthica does not seem to be disturbed by oxazepam exposure. Similar observations have already been reported for fathead minnows exposed to diazepam (Lorenzi et al, 2014). However, it should be noted that hatching rates in control and the lowest concentration were significantly lower than expected.…”
Section: Discussionsupporting
confidence: 89%
“…Anxiolytics are known to affect mammalian reproduction (Drobnis and Nangia, 2017;Guerriero and Fox, 1976;McElhatton, 1994), but surprisingly little is known about their toxicity to aquatic organisms. A few studies have shown that diazepam decreases social interactions in zebrafish (Danio rerio) (Giacomini et al, 2016), but no significant impact of this drug on reproductive behavior in fathead minnow (Pimephales promelas), or of oxazepam in Atlantic salmon (Salmo salar) (Hellström et al, 2020;Lorenzi et al, 2014) was reported. In addition, exposure to carbamazepine and diazepam has been shown to increase the total number of offspring in Daphnia magna (Rivetti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish (Danio rerio) such novel tank diving test results would be considered indicative of an increased anxiety-like state and/or a sedative effect (Cachat et al, 2010), but as the authors point out, fathead minnows may not respond in the same way (Huerta et al, 2016). Reproductive behavior of fathead minnows appears unaffected by a 21-day exposure to diazepam (0.1, 1.04 or 13.4 µg L -1 ) (Lorenzi et al, 2014). Taken together, these studies provide evidence that oxazepam can induce anxiolytic effects in wild fish populations close to WWTP outlets, although species differ in sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lorenzi et al. 2016 found that fathead minnow ( Pimephales promelas ) reproduction was increased when fish were exposed to 0.1 µg/L of diazepam and not the higher doses. It is clear that plasma cortisol, one mechanism by which oxazepam may induce its effects.…”
Section: Discussionmentioning
confidence: 99%